Study of physical fitness indicators in female athletes in artistic and aesthetic gymnastics: a comparative analysis - Erkomayshvili, I.V.; Lebedihina, T.M.; Semenova, G.I.; Kostinyuk, V.S. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to conduct a comparative assessment of the physical fitness indicators of female athletes in sports improvement groups in artistic and aesthetic gymnastics. Methods and structure of the study. The research was conducted at the Gracia Sports School in Ekaterinburg, with the participation of 14 gymnasts aged 14-15 who were competing at the sports improvement stage (7 of them were involved in artistic gymnastics and 7 in aesthetic gymnastics). To assess the level of preparedness, standards for general and special physical training approved by the Federal Standards of Sports Training for the sports of ‘artistic gymnastics’ and ‘aesthetic gymnastics’ were used. Results and conclusions. Based on the results obtained, it was found that aesthetic gymnasts have higher physical fitness indicators compared to artistic gymnasts. The most significant differences are observed in strength and endurance indicators. It is assumed that the results will be useful for identifying dominant physical qualities, managing the training process, selecting athletes when transitioning from artistic to aesthetic gymnastics, and making changes to the training process planning in national teams for these types of gymnastics.